Characteristic of Evaluation in Learning Arabic Language at Islamic Boarding School Anwarul Huda Malang - Ahmad Jaunanto; Hanik Mahliatussikah (Alsuna: Journal of Arabic and English Language, 2020)
Purpose - This study aims to describe the evaluation of Arabic language learning at boarding school Anwarul Huda Malang. Design/methodology/approach - This study used is qualitative research, and the data of this study are the teachers who teach in Islamic boarding school Anwarul Huda Malang and the method of data collection using interview and observation. Findings - The study describes the evaluation of the Arabic learning assessment at the Anwar Al-Huda Malang Institute which was carried out twice, namely the midterm and final semester exams. The first form of the exam is by reading a book in the midterm, and the final is by filling out an answer sheet, namely a written exam. The evaluation tools used are multiple test questions, true and false questions, and short answer test questions. Originality/value – Learning evaluation should be continuity. This means that if it is tested at the beginning by reading a book, it should also end by reading a book. It is enough that the question points need to be changed. Paper type – Research Paper